Peran Konselor dalam Mengatasi Kecemasan melalui Konseling Individu pada Siswa MAN 2 Pamekasan - Imam Wahyudi Firnanda; Fathol Haliq (Jurnal DinamikA, 2026)
This study aims to describe the role of counselors in addressing student anxiety through individual counseling services at MAN 2 Pamekasan. The study employs a qualitative, descriptive approach. The informants consisted of 1 Guidance and Counseling (BK) teacher who handled individual counseling services and 5 students who had participated in individual counseling services related to anxiety issues. Data were collected through non-participatory observation, in-depth interviews with counselors and students, and documentation. The results of the study indicate that the forms of anxiety experienced by students include academic anxiety (regarding exams, assignments, and grades), social anxiety, and career anxiety. Individual counseling was conducted through the stages of assessment, contract planning, periodic sessions, and monitoring and evaluation. Factors influencing student anxiety included family factors (parental expectations), madrasah factors (workload, competition), and individual factors (perfectionism, low self-esteem). The counselor’s role is manifested in the functions of prevention, intervention, cross-party coordination, and professional capacity development. This study concludes that individual counseling using a cognitive-behavioral therapy (CBT) approach contributes to helping students manage academic anxiety. The implications for the development of guidance and counseling services in madrasahs are the need to strengthen counselors’ competencies and foster collaboration with teachers and parents.